Graft-versus-host disease-like erythroderma: a sign of recurrent thymoma. Issue 49 (December 2017) - Gui, Xiujuan; Zhu, Xinhai; Guo, Liangjun; Tan, Guoqiang; Liu, Yan; Tan, Yi; Chen, Qiufang; Song, Yuwei; Lin, Shaoqiang
Abstract: Rationale: Thymomas are associated with numerous autoimmune disorders, such as myasthenia gravis (MG), pure red cell aplasia (PRCA), and systemic lupus erythematosus (SLE). However, graft-versus-host disease (GVHD)-like erythroderma is a relatively uncommon paraneoplastic disorder associated with thymomas and signifies a poor prognosis. Patient concerns: A 35-year-old woman with medical history significant for stage IVa type AB thymoma presented with patchy erythema over face, trunk, and extremities that failed to respond to topical steroids. Diagnosis: A contrast-enhanced computerized tomography (CECT) scan of the chest demonstrated tumors in the right mediastinum and right pleura. Percutaneous right mediastinal pleural biopsy confirmed recurrent thymoma (WHO type B3, Masaoka stage IVb). Histopathologic examination of her skin lesions revealed GVHD-like erythroderma. Interventions: The patient received chemotherapy and local thoracic radiotherapy, as well as corticosteroids. Outcomes: The eruptions gradually subsided with hyperpigmentation; however the patient eventually died of multiple organ failure. Lessons: GVHD-like erythroderma is an uncommon paraneoplastic disorder associated with thymomas. Though its pathogenesis still needs further research, prompt diagnosis and appropriate treatment can improve survival rate in patients.